PENGARUH MEKANISME CORPORATE GOVERNANCE TERHADAP KONSERVATISME AKUNTANSI - Frans Dwiki Gabriel Rajagukguk; Abdul Rohman (Diponegoro Journal of Accounting, 2020)
The purpose of study was to examine the effect corporate governance mechanism on accounting covervatism at financial company.This research using a sample of 185 financial companies listed on the Indonesian Stock Exchanged in periode 2016-2018. Sampling was done using a purposive sampling method and then the analisis technique used multiple regression analyze. The result of this research show the board of commisioners, public ownership and the types of auditor has a negative effect and then independence of the board of commisioners have a effect positive on accounting conservatism.